A Structural and Semantic Analysis of English Loanwords in Mandarin on Weibo - Cicik Arista; Harisa Ismi Dina (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study presents a structural and semantic analysis of English loanwords in Mandarin on Weibo. Although previous research has extensively investigated phonological adaptation and etymological origins, the structural patterns and semantic meanings of English loanwords in Mandarin in digital communication remain underexplored. This study aims to describe the structural formation based on Xing's classification and denotative/connotative meanings based on Barthes' semiotic framework. A qualitative descriptive approach was employed. Data were collected from Weibo posts in the fourth quarter of 2025 through non-participatory observation and web scraping, resulting in 150 English loanwords in Mandarin for analysis. The findings reveal three structural patterns. Full phonetic translation dominates, followed by phonetic translation with a Mandarin morpheme, while mixed sound-meaning translation occurs least often. This distribution indicates that phonological adaptation is the primary strategy for loanword formation on social media. Regarding meaning, connotative meaning was identified through contextual analysis of metaphorical, slang, or culturally charged expressions within each post, such as 披萨 (pīsà/pizza) used to express romantic feelings in fan community posts. Denotative meaning was assigned when the loanword referred literally to its dictionary definition. Denotative use is more prevalent than connotative use, suggesting that Weibo users primarily employ loanwords for referential purposes. Connotative meanings, though fewer, are significant as they demonstrate creative repurposing for emotional and cultural expression. The study contributes to Mandarin language teaching by showing how English loanwords can serve as accessible vocabulary and how understanding connotation helps learners grasp cultural nuances in digital communication.